Chief Executive Officer Equity Incentives and Accounting Irregularities - ARMSTRONG, CHRISTOPHER S.; JAGOLINZER, ALAN D.; LARCKER, DAVID F. (Journal of Accounting Research, 2010)
ABSTRACT This study examines whether Chief Executive Officer (CEO) equity‐based holdings and compensation provide incentives to manipulate accounting reports. While several prior studies have examined this important question, the empirical evidence is mixed and the existence of a link between CEO equity incentives and accounting irregularities remains an open question. Because inferences from prior studies may be confounded by assumptions inherent in research design choices, we use propensity‐score matching and assess hidden (omitted variable) bias within a broader sample. In contrast to most prior research, we do not find evidence of a positive association between CEO equity incentives and accounting irregularities after matching CEOs on the observable characteristics of their contracting environments. Instead, we find some evidence that accounting irregularities occur less frequently at firms where CEOs have relatively higher levels of equity incentives.